2014
DOI: 10.1177/1045389x14549871
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a piezoelectric beam subjected to water droplet impact with water layer formed on the surface

Abstract: Rain impact energy harvesting using piezoelectric energy harvester has gained much attention recently. However, previous works have only considered the effect of single water droplet. In the case of raindrop, water would accumulate on the surface of the energy harvester and form a shallow water layer. This article models the dynamics of a piezoelectric beam, served as a raindrop energy harvester, subjected to water droplet impact with water layer formed on the surface. The impact of water droplet on the tip of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
0
17
1
Order By: Relevance
“…Furthermore, while the stiffer cantilever oscillated at its natural eigenfrequency ( f 0 = 112 Hz), the softer substrate showed an additional higher order oscillation ( f 0 = 11 and f 1 = 68 Hz). The time scales of droplet spreading and recoil (~10 ms) were much shorter than the first order oscillation timescale (~100 ms) for the low stiffness substrate, resulting in the inability to accelerate the droplet upwards (see Supplementary Video S6 ), and enabling full droplet recoil before lift-off with similar contact times as those on a rigid superhydrophobic surface 21 22 . To enable contact time reduction, our results show that the substrate oscillation and droplet impact timescales must be on the same order of magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, while the stiffer cantilever oscillated at its natural eigenfrequency ( f 0 = 112 Hz), the softer substrate showed an additional higher order oscillation ( f 0 = 11 and f 1 = 68 Hz). The time scales of droplet spreading and recoil (~10 ms) were much shorter than the first order oscillation timescale (~100 ms) for the low stiffness substrate, resulting in the inability to accelerate the droplet upwards (see Supplementary Video S6 ), and enabling full droplet recoil before lift-off with similar contact times as those on a rigid superhydrophobic surface 21 22 . To enable contact time reduction, our results show that the substrate oscillation and droplet impact timescales must be on the same order of magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…The water layer increases until it reaches the edges of the harvester and there is a spill. This unsteady behavior has some important effects on harvester dynamics [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…When there is a water layer of sufficient depth on the harvester surface, the impact of raindrops generates water ripples that causes additional gravity loads on the harvester surface [17].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, a distributed parameter model is advantageous which allows to accurately predict the electromechanical behaviors of the beam by means of accurate strain distribution. Based on the model developed by Sodano et al [ 30 ] using Rayleigh–Ritz theorem and Hamilton’s principle, Wong et al [ 31 ] tried to model both the impact force of droplet and the force generated by the water ripple on a PZT cantilever through applying the distributed parameter method. Results showed that the presence of water layer on an untreated beam surface decreased the dominant frequency so as the voltage output.…”
Section: Introductionmentioning
confidence: 99%